2018
DOI: 10.1021/acsami.8b11229
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Flexible Photosensors with GaN Nanowires Horizontally Embedded in a Graphene Sandwich Channel

Abstract: In this study, we report highly efficient and flexible photosensors with GaN nanowires (NWs) horizontally embedded in a graphene sandwich structure fabricated on polyethylene terephthalate. GaN NWs and the graphene sandwich structure are used as light-absorbing media and the channel for carrier movement, respectively. To form uniform high-quality crystalline GaN NWs on Si(111) substrates, the initial nucleation behavior of the NWs was manipulated by applying the new growth technique of Ga predeposition. High-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…The spatial densities of GaN NWs for the photosensors are almost the same. In addition, the effect of the length and spatial density of GaN NWs on the device performances of the photosensors was reported in our previous work …”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…The spatial densities of GaN NWs for the photosensors are almost the same. In addition, the effect of the length and spatial density of GaN NWs on the device performances of the photosensors was reported in our previous work …”
Section: Methodsmentioning
confidence: 85%
“…The average diameter and height of the undoped GaN NWs were measured as 63.8 ± 1.3 nm and 1.1 ± 0.1 μm, respectively. High-resolution TEM images and diffraction patterns obtained along the vertical direction of GaN NWs showed that stacking faults were rare . This indicates the formation of high-crystalline GaN NWs.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations